Pengaruh Insentif terhadap Prestasi Kerja Karyawan Sales pada Dealer Banyuwangi Motor Genteng (The Influence of Incentive to the Work Performance of Sales Employee at Banyuwangi Motor Dealer, Genteng) - Rukmana, Yulyta Indra; Wahyuni, Sri; Pramono, Rudy Eko (e-Sospol, 2019)
AbstractDea ler B an y u w ang i M o t o r is a c o m p an y e ng a g i n g in t h e s e r vice s ect o r es p e c i a lly in p ro vi d i n g a n d s elli n gm o t o r ve h icles H ond a b r and f o r c on s u mer s In c en tive c o n t a i n s a p r o fe s s i ona l r e l a ti on s h i p T h eem p l o y ee' s goa ls to w o r k a r eto f u lfill t h e em p l o y ees' life n e ed s an d to im p l e m e n t t h e c o m pany' s mi s s i o na n d vi s i o n T h e r e f o r e, em p l oy ees w ill b e r e w a r d ed in t h e f o r m o f i n c en tivewhich is su it ab le w i t h t h eir wor kpe r f o r m a n ce a n d c o m p any Re qu i r em en t s T h is r e s e a r c h w a s a imed to k no w t h e effe c t o f i n c en tive o n s a lesem p l o yee s w o r k p e r f o r m a n ce at De a ler B a n y u w ang i M o t o r i n Ge n te ng . T h e a m o u n t o f i n c en tive g iven b yt h e c o m p an y to s a les em p l o y e es w a s ba s ed o n t h e a c h i e vi n g t a r g et lev e l in e a c h m on t h w ith e a ch s a l e spo s iti on . Sa les em p l o y e es’ w o rk p erf o r m an ce w a s s e e n f r o m t h e quan tity a c h iev e d t h a t w a s t h e t a r g etw h ich excee d ed t h e c o m p a n y s r e qu i r eme n ts an d t h e t a s k e xec u ti o n b y p r o vi d i n g p r od u ct i n f o r m a ti o nf r o m t h e c o m p an y to p r o s p e c tive c u s t o m e r s . T h is quan tit a tiv e r ese a r c h e m p l o y e d e xp l a na t ive app r oach 3 9r es po nd e n ts w ere d etermi n ed b y u s i n g s im p le li n e a r r e g r e ss i o n ana lys is T h e me a s u reme n t tec h n i q u e int h is r e s e a r c h w a s li k e r t s c a le. T h e da ta w e re ana lyzed b y u s i n g v a li d ity t e s t, r eli ab ility t e s t, s im p leli n i er r e g r e s s i o n ana lysi s h y po t h esis te s t, an d c o effic ie n t o f d etermi na ti o n R2 T h e r e s e a r ch r es u ltsi nd ic a ted t ha t i n c en tive h a d a s i gn ifi c an t effe c t o n s a les em p l o y e e s ’ w o r k p erf or m an ce a t De a l e rB an y u w a n g i M o t o r in Ge n te ng . Hy p o t h esis v a l u e te s t ob t a i n ed t ha t i n c e n tive v a l u e ha d t c o u n t t t a bl e2 3 5 7 2 02 6 a n d t h e s i gn ific a n ce v a l u e w a s 0 0 2 4 0 05 T h eref o r e, H0 w a s r ejecte d , an d Ha w a sa c c e p te d T h e C o efficie n t V a l u e R 2 o f In c e n t ive v a r i ab le X to W o r k Ac h ie v eme n t Y v a r i ab le w a se qua l to 0 1 31 . T h is v a l u e i nd ic a ted t ha t i n c en tive a ffect e d w o r k p e r f o r m a n ce a s m u ch a s 13 1 %w h i le t h e r em a i n i n g 86 9 w a s i n fl u e n c e d b y o t h er f a ct o r s excl ud e d in t h is r e s e a r c h.Key w o r d s i nc e n tive, w o r k p e r f o r m a n ce s a les e m p l o y e es